Bariery integracji uczniów cudzoziemskich ze środowiskiem szkolnym - Baranowsk, Aneta Sylwia (Studia Edukacyjne, 2020)
Every year, more and more immigrants come to Poland. They settle in our country together with their school-age children. One of the tasks that immigrants and their children face is integration into Polish society. In the case of foreign children, it usually takes the form of integration into the school environment as they have the most frequent contact with the Poles at school. Integration into the school environment involves the inclusion of immigrant students in the social life of the school and simultaneously opening up the entire school community to their presence. Unfortunately, culturally different children encounter many obstacles, which significantly impedes success. These obstacles relate primarily to the lack of knowledge of the Polish language, emotional problems and a negative attitude towards their peers and their parents as well as to the teaching staff.